Self reported symptoms and inhibition of acetylcholinesterase activity among Kenyan agricultural workers. Issue 3 (1st March 2000) - Ohayo-Mitoko, Grace J A; Kromhout, Hans; Simwa, James M; Boleij, Jan S M; Heederik, Dick
Abstract : OBJECTIVES: This study was part of the East African pesticides project. The general objective was to assess health hazards posed by handling, storage, and use of pesticides, on agricultural estates and small farms with a view to developing strategies for prevention and control of pesticide poisoning. The aim of this paper is to describe the prevalence of symptoms in this population, to relate levels of inhibition to reported symptoms and evaluate at which levels of inhibition symptoms become increased. METHODS: Complete data were available for 256 exposed subjects and 152 controls from four regions in Kenya. A structured questionnaire on symptoms experienced at the time of interview was given to all subjects and controls. Information was also obtained on sex, age, main occupation, and level of education. Symptoms reported during the high exposure period, were initially clustered in broader symptom categories from reference literature on health effects of pesticides that inhibit cholinesterase (organophosphate and carbamate). Prevalence ratios were estimated for symptoms with changes in cholinesterase activity in serum. RESULTS: Symptom prevalence in exposed subjects was higher during the high exposure period than the low exposure period, although these differences were not significant. Interestingly, a clear and significant change in symptoms prevalence was found in the controls with a higher prevalence in the low exposure period. Analysis of the relation between cholinesterase inhibition and symptoms showed that prevalence ratios were significantly >1 for respiratory, eye, and central nervous system symptoms for workers with >30% inhibition. Similar results were found for analyses with the actual level of acetylcholinesterase activity. CONCLUSION: The results suggest the presence of a relation between exposure and acetylcholinesterase inhibition, acetylcholinesterase activity, and respiratory, eye, and central nervous system symptoms. Increased symptom prevalence was found at acetylcholinesterase activities generally considered to be non-adverse.